Exercising Intercultural Performance in Adaptations: Regional Kerala Myths and Rituals used as tool in Shakespeare film adaptation in Kannaki and Karmayogi (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Integral to the concept of "interculturalism" is an appreciation and knowledge of many cultural backgrounds. The major emphasis of intercultural performances is the equitable and meaningful interchange of performance standards and conventions. The timeless universal truths about mankind found in William Shakespeare's plays ensure that they remain relevant and influential even in our own day. Shakespearean plays are more amenable to adaptation into any genre because of their adaptability and flexibility as well as their inherent humanism. There is a lengthy history of retelling great stories in Malayalam film. The literary shifts, thematic echoes, and cultural subtleties that set apart the two film versions of Shakespeare's tragedies, "Hamlet" and "Antony and Cleopatra," from one another are the subject of this research. The exotic customs of Kelipathram and Poorakkali from Kerala have been included into the film to emphasize the cultural superiority of the Orient over the Occident. Shakespeare's Cleopatra continues to evoke mixed feelings in modern audiences; some see her as a manipulative force, while others find her aesthetically pleasing. Whatever your opinion, it's clear that Cleopatra defies categorization within patriarchal society's narrow definitions of women. The film's director gave Kannaki a mysterious air. Kannaki successfully achieves the characteristic of cinematic appropriation by meticulously blending mythological, cultural, geographical, and semiotic aspects within the narrative realm of Antony and Cleopatra. As a result, the director alludes to Antony and Cleopatra's politics inside Kannaki's oriental poetics.